2013
DOI: 10.5993/ajhb.37.5.8
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Trends in Alcohol Use: The Value of a Surveillance System

Abstract: This study presents multiple consumption-related variables over time and has highlighted important demographic variations in alcohol consumption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Our study reports Australian-born participants being more likely to report higher alcohol consumption than both the comparison groups. While Australian alcohol consumption rates are going down [ 37 ], overall rates are still relatively high and especially among baby boomer populations [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study reports Australian-born participants being more likely to report higher alcohol consumption than both the comparison groups. While Australian alcohol consumption rates are going down [ 37 ], overall rates are still relatively high and especially among baby boomer populations [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It suggests that further education and greater financial means are associated with a social position where drinking is potentially more affordable and where moderation is socially acceptable [35,36]. Drinking behaviour is widely considered to be agerelated, and often characterised by heavier episodic drinking during early adulthood, more frequent but lower overall consumption in mid-to-late adulthood [11,37], followed by increased prevalence of abstinence in later life [23]. Recent studies have also shown that the transition to abstinence in later life is not as widespread as in previous generations [19].…”
Section: Discussionmentioning
confidence: 99%
“…Even less is known about the attributes of low-risk drinkers who neither drink at levels associated with long-term nor short-term harm. Many Australian studies investigating the association between socio-demographic dimensions and alcohol use among adults have focused on elevated levels of drinking and the potential of long-term harm [7], short-term harm [8,9], or both [10][11][12][13]. In such analyses, the exact configuration of the group to which risky drinkers are compared is often unclear [7,8,10,12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…No analysis was undertaken assessing the differences by demographic characteristics. Demographic differences in alcohol consumption was undertaken in a previous publication [54] . Other weaknesses have been documented more fully in a previous publication [54] .…”
Section: Discussionmentioning
confidence: 99%